Perceived Discrimination, Racial Identity, and Multisystem Stress Response to Social Evaluative Threat Among African American Men and Women - Todd Lucas; Rhiana Wegner; Jennifer Pierce; Mark A. Lumley; Heidemarie K. Laurent; Douglas A. Granger (2016)
Understanding individual differences in the psychobiology of the stress response is critical to grasping how psychosocial factors contribute to racial and ethnic health disparities. However, the ways in which environmentally sensitive biological systems coordinate in response to acute stress is not well understood. We used a social-evaluative stress task to investigate coordination among the autonomic nervous system, hypothalamic-pituitary-adrenal axis, and immune/inflammatory system in a community sample of 85 healthy African American men and women.Six saliva samples, 2 at each of baseline, event, and recovery phases of the stressor task, were assayed for cortisol, dehydroepiandrosterone-sulfate, salivary alpha-amylase, and salivary C-reactive protein. Individual differences in perceived discrimination and racial identity were also measured.Factor analysis demonstrated that stress systems were largely dissociated before stressor exposure but became aligned during event and recovery phases into functional biological stress responses (factor loadings ≥ .58). Coordinated responses were related to interactions of perceived discrimination and racial identity: when racial identity was strong, highly perceived discrimination was associated with low hypothalamic-pituitary-adrenal axis activity at baseline (B's = .68-.72, p < .001), low stress mobilization during the task (B's = .46-.62, p < .049), and a robust inflammatory response (salivary C-reactive protein) during recovery (B's = .72-.94, p < .002).Culturally relevant social perceptions may be linked to a specific pattern of changing alignment in biological components of the stress response. Better understanding these links may significantly advance understanding of stress-related illnesses and disparities.